Selective Arterial Embolization (SAE) in Aneurysmal Bone Cyst (ABC) (Annals of Medical Research, 2021)
Aim: The aim of the study was to evaluate the success of selective arterial embolization (SAE) treatment in aneurysmal bone cysts (ABC).Materials and Methods: Patients were referred to our clinic between January 2013 and December 2019 with a pathological diagnosis of ABC were analyzed retrospectively. The study was completed with 18 patients (9 male, 9 female) (7-59 years). Six ABCs were located in the axial skeleton and twelve were in the appendicular skeleton. SAE was done with particulate or liquid embolic agents with a coaxial catheter system. Demographic data of the patients, and the correlation between lesion size and total embolization were analyzed. Complications related to the angiographic procedure were also examined. Patients were considered as complete responders if no recurrence was noticed at two-year follow-up after SAE. Patients with shorter follow-up without recurrence were considered asymptomatic; p 0.05 was considered as statistically significant.Results: In this study population, a single embolization was performed in ten patients (55.56%), two consecutive embolizations in six patients (33.33%), and three consecutive embolizations in two patients (11.11%). A low correlation was observed between embolization numbers and lesion sizes (k= 0.35). The mean follow-up period of the patients who underwent SAE was 33.76 months (6-61 months). The treatment response was achieved in 88.9% (n: 16) of the patients who received SAE. Surgery was performed in two patients (11.1%) due to recurrence. There were no major complications recorded such as skin necrosis or paresthesia.Conclusion: Due to its low complication rates, easy reproducibility, and similar success rate with surgery, SAE is a reliable method for the treatment of ABC.
Keywords: Aneurysmal bone cyst; embolization; selective arterial embolization